Institutional and Academic Transcripts of Police Interrogations - Komter, Martha (Frontiers in Communication, 2022)
The effects of working circumstances and intended uses on the transcripts of police interrogations cannot be underestimated. In the Netherlands, police transcripts are usually drawn up in the course of the interrogation by the interrogator or, when two police officers conduct the interrogation, by the reporting officer. Contemporaneous transcription involves the interrogators in a complex configuration of interactional commitments. They have to find a way to coordinate the talk and the typing, they must transcribe the talk of an event they themselves participate in, they must do justice to the suspects' story while also taking into account the intended readership of the police report, and they must produce a document that can serve as an official piece of evidence in the criminal case. In studying recorded police interrogations and their transcripts I realized that my own transcripts are also related to their intended uses and to my working circumstances. My transcriptions are much more detailed than those of the police, which draws the attention to the differences between them. The most noticeable difference is that police transcripts focus on substance and mine on interaction. Police transcripts are meant to be evidence of the offence and mine of the talk. But there are also similarities. Both police transcripts and those of mine are selective. Police transcripts orient to their relevance for building a case, mine orient to their relevance for my research questions. Both police transcripts and those of mine treat the transcript as the talk it is meant to represent. For a criminal case this means that in court suspects are held accountable for what the police wrote down as their statement, which disregards the fact that the police transcript is a coproduction.